REDUKSI MAKSUD PRAGMATIK INSYA ALLAH DI KALANGANMASYARAKAT MUSLIM BERLATAR BELAKANG BUDAYA JAWADI SURAKARTA - SAPUTRO, ERWAN, Dr. Harun Joko Prayitno, M.Hum, Prof. Dr. Abdul Ngalim, MM., M.Hum (2017)
The objectives of this research are; (1) To identify the speech acts among the Moslems community having the Javanese cultural background in Surakarta by utilizing the lingual indicator of Insya Allah, (2) Describe the shift of the pragmatic meaning of Insya Allah among the Moslem community having the Javanese cultural background in Surakarta. This is a descriptive qualitative research. The subjects of the research are utterances used daily by the Moslems community in Surakarta whether in the workplaces, gatherings or process of bargaining during the trade. The objects of the research are the speech acts which contain the reduction of a pragmatic meaning of Insya Allah among the Moslems community having the Javanese Cultural background in Surakarta. The data of this research are in the forms of speech acts which contain the reduction of a pragmatic meaning of Insya Allah among the Moslems community having the Javanese cultural background in Surakarta. The techniques of collecting the data are observation which is used to observe the forms of speech acts done by the Moslems community having the Javanese cultural background in Surakarta. The speech acts which are observed are those which contain the reduction of the pragmatic meaning of Insya Allah. The results of the research show (1) The forms of the speech acts among the Moslem community having the Javanese cultural background in Surakarta using the lingual marker of Insya Allah are categorized into six, namely; uncertainty (27,5%), hope (10%), certainty (37,5%), soft refusal (7,5%), same ignorance (10%), and ignorance(7,5%). (2) The reduction meaning of pragmatic Insya Allah in this research is meant to maintain the hospitality not to offend and disappoint other parties and vice versa.